Measurements of structural and optical properties for (AgPO3)1-x(Ag2SO4)x glasses. (28th January 2022) - Zaki, A. A.; Aljarrah, Mohammad; Alkhazali, Atif; Salman, Fathy
ABSTRACT: The glass system of composition (AgPO3 ) 1-x (Ag2 SO4 ) x [where x = 0, 0.15, 0.20, 0.25 Mol%] was prepared using the conventional melt quenching technique. The molar volume and density were determined to characterise the structure of the glasses obtained. X-ray diffraction was used to confirm the amorphous nature of the glass samples used. The absorbance and transmittance were measured in the spectral range of 200–3000 nm for the prepared glasses by using UV-Vis two-beam spectrophotometer. A new modified equation has been formulated to determine the refractive index of the glasses used. Dispersive power, energy gap, dispersion energy and oscillator energy were measured as well. Also, molar refractivity, molecular polarisability and metallization criterion for the glass samples of different Ag2 SO4 concentrations were calculated.